MODEL PENINGKATAN KEMAMPUAN BAHASA INGGRIS UNTUK GURU SMK RSBI DI JAWA TENGAH - Widiyanto, Widiyanto (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
The purpose of this study was to find a model in improving RSBI vocational schools teachers’ English skills in Central Java. This study used research and development(R &D) design developed by Borg & Galland. It was a qualitative research; data were collected by interviews, questionnaires and observations to get the primary and secondary data. The study was located in Central Java focusing on RSBI Teachers’ English Skills. The benefit of the research was to provide an alternative in improving RSBI vocational schools teachers’ English skills. The result was a model product in improving RSBI vocational schools teachers’ English skills in Central Java. Thus, it is suggested for RSBI vocational teachers to improve their English skills by using this model.